Firm Size, Ownership and Profitability : Determinants Of Performance In The Malaysian Palm Oil Sector - Ong, Darryl Teck Jin (2003)
The Malaysian palm oil sector has been pegged by the Malaysian Government to be one of the focus areas for consolidation and restructuring in 2003. The Government’s aims are simple: 1) To create the world’s largest oil palm plantation company thereby leveraging economies of scale and hopefully become an efficient model for others to follow, 2) To enhance investors’ interest and increase tradability of the stock, and 3) To spearhead efforts in creating large capitalisation stock. As a result of this, recent events indicate that activities towards this aim may well be under way. Plans to merge PNB-owned plantation companies and the listing of FELDA on the KLSE have raised speculation and interest. Some industry observers are sceptical, however, because the PNB-owned companies and FELDA are not generally regarded as well-managed, with costs higher than average and outputs below average. The aim of this study is to analyse the effects of market structure components and other performance measures to better understand the dynamics and determinants of financial performance for firms within the Malaysian palm oil sector. Emphasis in this study directed toward understanding the effects of firm size and firm ownership on financial performance, which is proxied by profitability. The study disproves the classical notion that ‘big equals better’. Firm size was shown to have an inverse relationship with financial performance. Further, it was found that privately-owned firms outperform state-owned firms in the Malaysian palm oil sector. These outcomes have far reaching implications that contest the viability of the Malaysian Government’s current initiatives.